2015
DOI: 10.1093/ijnp/pyv046
|View full text |Cite
|
Sign up to set email alerts
|

Changed Synaptic Plasticity in Neural Circuits of Depressive-Like and Escitalopram-Treated Rats

Abstract: Background:Although progress has been made in the detection and characterization of neural plasticity in depression, it has not been fully understood in individual synaptic changes in the neural circuits under chronic stress and antidepressant treatment.Methods:Using electron microscopy and Western-blot analyses, the present study quantitatively examined the changes in the Gray’s Type I synaptic ultrastructures and the expression of synapse-associated proteins in the key brain regions of rats’ depressive-relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 64 publications
5
44
0
3
Order By: Relevance
“…We observed that escitalopram significantly enhanced dendritic outgrowth and increased dendritic spines in hippocampal neuron cultures exposed to Aβ 1-42 . Our previous study has reported that escitalopram rescued synaptic deficits in depressive-like rats [ 41 ]. Moreover, several studies have revealed that the disturbance of synaptic plasticity recovered when tau hyperphosphorylation was reversed pharmacologically or with genetic technology [ 39 , 40 ], consistent with our results.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that escitalopram significantly enhanced dendritic outgrowth and increased dendritic spines in hippocampal neuron cultures exposed to Aβ 1-42 . Our previous study has reported that escitalopram rescued synaptic deficits in depressive-like rats [ 41 ]. Moreover, several studies have revealed that the disturbance of synaptic plasticity recovered when tau hyperphosphorylation was reversed pharmacologically or with genetic technology [ 39 , 40 ], consistent with our results.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic administration of another SSRI (escitalopram) decreased the length of the active zone of synapses that was increased by CUMS. In addition, escitalopram was able to restore spinophilin levels that were decreased in BLA after CUMS ( Li et al., 2015 ).…”
Section: Antidepressant Drugs Stress and The Amygdalamentioning
confidence: 99%
“…it was reduced, pointing to increased synaptic gain in the DGpl. The relationship between reduced synaptic cleft width and impairment of spatial memory appears counterintuitive, given the common association of increased synaptic cleft width and negative behavioural phenotypes 50 51 . However, it needs to be kept in mind that it depends on the brain area investigated, its network structure and the functions of the neurons involved whether increased synaptic transmission efficiency translates into beneficial or adverse behavioural effects.…”
Section: Discussionmentioning
confidence: 99%